2020
DOI: 10.7759/cureus.9309
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Cannabis Use and Schizophrenia: Causative or Curative? A Systematic Review

Abstract: Marijuana is one of the most abused substances in the world. Marijuana is getting legalized around the world. So, it is crucial to understand its effect on our mental health. Its impact on the schizophrenia spectrum needs our special attention. Even though marijuana has been around for a long time, its exact effects are still unknown. Schizophrenia is a chronic illness affecting approximately 20 million people worldwide. Schizophrenia and cannabis seem to have a close relationship, and we want to explore this.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 15 publications
(70 reference statements)
1
24
0
4
Order By: Relevance
“…In consequence, although promising according to their authors, the studies’ results cannot constitute a source of fundamental knowledge. Rather, they can indicate potential directions for further, in-depth, well-structured research [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, although promising according to their authors, the studies’ results cannot constitute a source of fundamental knowledge. Rather, they can indicate potential directions for further, in-depth, well-structured research [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However unlike THC or cannabis extracts the second most abundant cannabis compound cannabidiol (CBD), does not exhibit psychotropic properties [65]. The association of cannabis with several mental disorders, particularly schizophrenia onset and progression, has been reported [66]. Interestingly, this association was also observed at the molecular level through proteomic analysis.…”
Section: Proteomic Studies On Cannabismentioning
confidence: 99%
“…CBD was reported to have milder psychoactive properties and fewer side effects than THC and a growing number of studies have reported its beneficial effects in comparison to the adverse effects associated with THC [66,105]. Therefore, CBD appears to be a desirable agent for medical purposes, yet only a limited number of proteomic studies have been performed thus far.…”
Section: Proteomic Studies On Cannabidiolmentioning
confidence: 99%
“…We also know that patients with schizophrenia use cannabis as self-medication to relief depressive states, anxiety and social inhibition. It is the tetrahydrocannabinol part of cannabis that probably induce psychosis [ 13 , 14 ]. Most studies have explored the relationship between cannabis and depression and a review article from 2014 concluded that cannabis use is associated with a greater risk of developing depression [ 15 ].…”
Section: Introductionmentioning
confidence: 99%